2018
DOI: 10.4081/mr.2018.7480
|View full text |Cite
|
Sign up to set email alerts
|

Study on antibacterial and flavonoid content of ethanolic extract of Punica granatum (pomegranate) peel

Abstract: Pomegranate is known for it's many health benefits. These benefits are due to the biological active compounds which are present in the pulp as well as in the peel of the pomegranate. The active compounds from the peel were obtained using cold percolation method using ethanol as solvent. Antibacterial activity of pomegranate peel extract (PPE) was studied on E.coli, E. coli NCIM 2065, Salmonella typhi, Salmonella paratyphi B, Pseudomonas aeruginosa, Proteus mirabilis, S. aureus, S. aureus NCIM2079, Shigella fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
1
8
1
Order By: Relevance
“…However, this was contrary to the findings of Nobakht et al [33] who reported highest activity of flavonoids on P. aerugionsa and no activity on S. aureus with mean and standard deviation zone of inhibition of 24.7±2.9 mm and 0.0±0.0 respectively. Jaisinghani et al [34] also reported higher antibacterial activity flavonoids in S. aureus than P. aeruginosa at 100-25 mg/mL concentration compared to 500 mg/mL of extract in this study. It was concluded by Singh et al [30] that flavonoid studied had higher activity against gram positive bacteria than gram negative in which P. aeruginosa had zone of inhibition of 16.33 mm and 18.33 mm in S. aureus.…”
Section: Antibacterial Susceptibility Study Of Crude Flavonoid Extractsupporting
confidence: 74%
“…However, this was contrary to the findings of Nobakht et al [33] who reported highest activity of flavonoids on P. aerugionsa and no activity on S. aureus with mean and standard deviation zone of inhibition of 24.7±2.9 mm and 0.0±0.0 respectively. Jaisinghani et al [34] also reported higher antibacterial activity flavonoids in S. aureus than P. aeruginosa at 100-25 mg/mL concentration compared to 500 mg/mL of extract in this study. It was concluded by Singh et al [30] that flavonoid studied had higher activity against gram positive bacteria than gram negative in which P. aeruginosa had zone of inhibition of 16.33 mm and 18.33 mm in S. aureus.…”
Section: Antibacterial Susceptibility Study Of Crude Flavonoid Extractsupporting
confidence: 74%
“…aureus and it was more effective against gram positive bacteria than gram negative. In the study carried by Jaisinghani et al, 2018. The inhibition zone was greater against S. Typhimurium than Staph.…”
Section: Discussionmentioning
confidence: 93%
“…In other studies, researchers found that PPE had an equivalent strength against S. aureus , Salmonella sp., E. coli , etc. [ 22 ]. The antibacterial activity of PPE was associated with its effect on impairing the membrane integrity of bacteria.…”
Section: Resultsmentioning
confidence: 99%